Glucosinolate turnover in Brassicales species to an oxazolidin-2-one, formed via the 2-thione and without formation of thioamide. (September 2018) - Agerbirk, Niels; Matthes, Annemarie; Erthmann, Pernille Ø.; Ugolini, Luisa; Cinti, Susanna; Lazaridi, Eleni; Nuzillard, Jean-Marc; Müller, Caroline; Bak, Søren; Rollin, Patrick; Lazzeri, Luca
Abstract: Glucosinolates are found in plants of the order Brassicales and hydrolyzed to different breakdown products, particularly after tissue damage. In Barbarea vulgaris R.Br. (Brassicaceae), the dominant glucosinolate in the investigated "G-type" is glucobarbarin, ( S )-2-hydroxy-2-phenylethylglucosinolate. Formation of the nitrile from glucobarbarin was observed in vitro, while a previously suggested thioamide (synonym thionamide) was not confirmed. Resedine (5-phenyl-1, 3-oxazolidin-2-one) was detected after glucobarbarin hydrolysis in crushed B. vulgaris leaves and siliques, but not in intact parts. The abundance increased for several hours after completion of hydrolysis. The corresponding 1, 3-oxazolidine-2-thione (OAT), with the common name barbarin, was also formed, and appeared to be the precursor of resedine. Addition of each of two non-endogenous OATs, ( S )-5-ethyl-5-methylOAT and ( R )-5-vinylOAT ( R -goitrin), to a leaf homogenate resulted in formation of the corresponding 1, 3-oxazolidin-2-ones (OAOs), confirming the metabolic connection of OAT to OAO. Formation of OAOs was inhibited by prior brief heating of the homogenate, suggesting enzyme involvement. We suggest the conversion of OATs to OAOs to be catalyzed by an enzyme ("oxazolidinethionase") responsible for turnover of OAT formed in intact plants. Resedine had been reported as an alkaloid from another species - Reseda luteola L. (Resedaceae) - naturally containing the glucosinolate glucobarbarin. However, resedine was not detected in intact R. luteola plants, but formed after tissue damage. The formation of resedine in two families suggests a broad distribution of putative OATases in the Brassicales; potentially involved in glucosinolate turnover that needs myrosinase activity as the committed step. In agreement with the proposed function of OATase, several candidate genes for myrosinases in glucosinolate turnover in intact plants were discovered in the B. vulgaris genome. We also suggest that biotechnological conversion of OATs to OAOs might improve the nutritional value of Brassicales protein. HPLC-MS/MS methods for detection of these glucobarbarin products are described. Graphical abstract: Highlights: An oxazolidin-2-one, resedine, was formed during autolysis in three Brassicales species. A heat sensitive plant factor catalyzed turnover of oxazolidine-2-thiones to 2-ones. This reaction may be involved in glucosinolate turnover; candidate genes for the committed step identified. Extensive analysis failed to detect a previously reported glucosinolate-derived thioamide.